Common ownership model in the Roman private law - Uteubayev, T.T.; Kizdarbekova, A.S. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The features of development and implementation of ownership mechanism of legal regulation in the Roman private law, the principles of which were fully accepted by modern Kazakh law, and almost all modern European codifications are considered in the article. Originating as an exception, admitted by the Roman lawyers for regulation situations that cannot be ignored, over time, this Institute acquires all the features of the mechanism of legal regulation of common property, the classic form of which was share ownership. The author shows that the Roman lawyers in the relationship of common ownership put the emphasis on external relations exactly, emphasizing the material nature of this relationship, while the essence of corporate relations between owners themselves was ignored. The author considers that the lack of clear regulation of internal relations between co-owners and justify their relationship and determination the advantages with absolute external relations of the property was the main lacuna of legal regulation of common ownership in the Roman period, which gave rise a significant number of disputes between participants of common ownership. At the same time, the Roman lawyers developed system of protection of participant’s rights through actions aimed at ending of common property and compensation of expenses for the total thing and loss expenses incurred by the participants, which made it possible to resolve these disputes effectively. At the end of the work the author formulates the features of common ownership model in the Roman private law.
Рим жеке құқығындағы жалпы меншік үлгісі
Модель общей собственности в римском частном праве
Keywords: common ownership; participatory share ownership; limited interest; owner; common thing; agreement; the Roman private law; possession; use; disposal; property right